Fundamental study on the neutralization effect of grout using the carboxylate ester reactant - Hayashida, Akira; Endo, Munehito; Komiya, Kazuhito; Onishi, Takaaki; Shiozawa, Takuya (Japanese Geotechnical Society Special Publication, 2015)
The acid silica sol grouting material has been frequently used in the chemical grouting method. Recently, it has been recognized that the ground can contain high amounts of calcium carbonate (CaCO3), which are formed by deposits of shell and corals (high CaCO3 ground/soil). When using acid silica sol grout with a typical pH value of 2 to 4 in this type of ground, the chemical reaction of the excess acid in the grout reacts with the CaCO3 in the ground to produce carbon dioxide gas with foaming. Consequently, this chemical reaction reduces the strength and permeability of the ground. On the other hand, alkaline-based grout does not produce CO2 bubbles when there high levels of CaCO3 are present in the ground, because there is no excess acid in the grout. However, the used of alkaline-based grout cannot be expected to improve durability after gelation because of the large amount of alkali components. Therefore, it is neseccary to develop a grout that is more durable and does not cause CO2 foaming in the high CaCO3 ground. In this study, we investigated the physical properties of chemical grout agents mixed with a sodium silicate solution and acid carboxylic ester, controlling the duration of the gel time and CO2 foaming. We compared the strength characteristics of sand-gel with sand-gel specimens using two sample soils: Tohoku silica sand No.6 and high CaCO3 soil. Shrinkage and leaching tests were conducted to assess the durability of homo-gel.